Answer:
3) [tex]\sqrt{5}[/tex]
4)[tex]5\sqrt{13}[/tex]
Step-by-step explanation:
distance between two points:
[tex]d = \sqrt{(x_{2}-x_{1})^{2}+ (y_{2}-y_{1})^{2}}[/tex]
we have:
3) (6, -2), (8, -3)
[tex]x_{1} = 6[/tex]
[tex]y_{1} =-2[/tex]
[tex]x_{2} = 8[/tex]
[tex]y_{2} =-3[/tex]
so we have:
[tex]d =\sqrt{(8-6)^{2}+ (-3-(-2))^{2}}\\\\d =\sqrt{(2)^{2}+ (-1)^{2}}\\\\d = \sqrt{4+ 1}\\\\d=\sqrt{5}[/tex]
4) (7,-8), (-8, 2)
[tex]x_{1} = 7[/tex]
[tex]y_{1} =-8[/tex]
[tex]x_{2} =-8[/tex]
[tex]y_{2} =2[/tex]
[tex]d =\sqrt{(-8-7)^{2}+ (2-(-8))^{2}}\\\\d =\sqrt{(-15)^{2}+ (10)^{2}}\\\\d = \sqrt{225+ 100}\\\\d=\sqrt{325}\\\\d=5\sqrt{13}[/tex]